Gender Stereotype in Joyce Lebra’s The Scent of Sake - Arifatin, Fais Wahidatul (NOTION: Journal of Linguistics, Literature, and Culture, 2019)
Gender stereotype should be understood as negative beliefs shared by a particular group due to over-simplification and generalization. In this study, gender stereotype is used to mean negative beliefs toward women, which is based on their sexual or gender identity instead of their personal quality and individual competence. The writer try to show that in The Scent of Sake by Joyce Lebra is considered as a novel depicting the issue of gender stereotype in Japanese family culture, especially in managing the sake business which is represented trough Rie as the main character. Hence, in this study try to answer What are gender stereotypes experienced by Rie as reflected in Joyce Lebra’s The Scent of Sake and how does Rie struggle against gender stereotype as reflected in the novel. The research design used by the writer is literary criticism; it is liberal feminism especially the theory of Mary Wollstonecraft. The results of the study show that women as represented by Rie, is stereotyped in the family’s sake business through many negative stigmas. Such stereotypes have given negative influences toward Rie in terms of marginalization in management, in educational access and women’s lack of decision making in marriage. To reduce the effects, Rie struggles against gender stereotype by performing the stereotypes. Through considerable struggles, Rie has proven that women should not be viewed as inferior to men. Rie has tried very hard to play an active role as a subject in her own family’s business of sake production.